2020
DOI: 10.1177/1934578x20911764
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Optimization of Galla Turcica Polysaccharides and Determination of Its Antioxidant Activities In Vitro

Abstract: Though natural polysaccharides commonly show antioxidant activities, the current research on the isolation of polysaccharides from Galla Turcica and their antioxidant activities still remain as an ongoing challenge. In this work, response surface analysis was employed to optimize an ultrasonic-assisted extraction method for polysaccharides of Galla Turcica. Their antioxidant and free radical scavenging activities were then evaluated using 2,2-diphenyl-1-picrylhydrazyl, 2,2′-azino-bis(3-ethylbenzothiazoline-6-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Methanol solutions of compounds 1-8 and vitamin C were prepared in concentrations of 0.01, 0.02, 0.05, 0.1, 0.25, and 0.5 mg/mL, and 2,2-diphenyl-1-picrylhydrazyl (DPPH) in a concentration of 0.2 mmol/L DPPH. 22,23 One hundred microliter DPPH working solution was mixed with 100 μL of either vitamin C solution or test compound solution and stored at room temperature away from light for 30 min. Then, the absorbance was measured at 517 nm.…”
Section: Dpph Free Radical Scavenging Assaymentioning
confidence: 99%
“…Methanol solutions of compounds 1-8 and vitamin C were prepared in concentrations of 0.01, 0.02, 0.05, 0.1, 0.25, and 0.5 mg/mL, and 2,2-diphenyl-1-picrylhydrazyl (DPPH) in a concentration of 0.2 mmol/L DPPH. 22,23 One hundred microliter DPPH working solution was mixed with 100 μL of either vitamin C solution or test compound solution and stored at room temperature away from light for 30 min. Then, the absorbance was measured at 517 nm.…”
Section: Dpph Free Radical Scavenging Assaymentioning
confidence: 99%
“…The cynipid galls have been used in folk medicine owing to their therapeutic properties since ancient times (Oefele, 1933;Schimitschek, 1953;Imtiyaz et al, 2013;Iminjan et al, 2014;Elham et al, 2021). Much research on cynipid gall extracts in the last two decades has revealed various biological activities of the cynipid galls (Gao et al, 2018;Iylia Arina & Harisun, 2019;Azmaz et al, 2020;Hu et al, 2020;Kılınçarslan Aksoy et al, 2020;Yusof & Abdullah, 2020). It is very important to determine the phytochemical (phenolic compound, flavonoid etc.)…”
Section: Introductionmentioning
confidence: 99%